The analysis of the problems posed by prospective mathematics teachers about 'ratio and proportion' subject - ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2015)
Problem posing means either posing new problem situations in terms of given conditions or re-formulating an already written problem. In this study, the aim is to evaluate problems written by prospective mathematics teachers about ratio and proportion subjects in terms of criteria specified according to problem posing methods. According to this purpose, 'Problem Posing Form about Ratio and Proportion Subject' including questions for determining the tasks of free problem posing, semi-structured problem posing, structured problem posing and for determining which one is the most challenging problem posing task, was developed by the researchers. The data form was applied to 45 sophomore students who are studying in Kocaeli University, Teaching Primary School Mathematics department. The data collected throughout this study was evaluated by considering; i) Problem text (language and expression), ii) The compatibility of the problem with the mathematical principles, iii) The type/structure of the problem and iv) The solvability of the problem. In conclusion, it was concluded that prospective mathematics teachers posed clear and understandable problems which are compatible with the mathematical principles in the form of activity and which can be solved by students. The challenging sides of problem posing appeared as the hesitation on posing problems which are suitable to students' levels, the difficulty in remembering the subject clearly and not having sufficient information about problem posing. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Ratio; proportion; problem posing; analysing posed problems